Upaya Penurunan Emisi Gas Buang pada Mesin Bensin Sistem Bahan Bakar Konvensional Menggunakan Catalytic Converter Almunium untuk Kenyamanan Praktikum - Erman Erman; Sugiarto Sugiarto (Jurusan Teknologi Pertanian, 2020)
To reduce air pollution containing toxicity from the otto engine of a conventional fuel system (carburetor), an internal combustion device is used called a catalytic converter. Catalityc Converter uses the function to reduce levels of Hydrocarbon (HC), Carbon Monoxide (CO), and Nitrogen Oxide (NOX) emissions by oxidizing and reducing these substances to CO2, H2O and N2 which are environmentally friendly. However, the price is expensive and difficult to get it, not all motor vehicles use this technology. Because the catalyst is made of precious metals such as Palladium, Platinum and Rhodium. One of the efforts made is to make catalyst from Almunium Al material, which is easily obtained and the price is relatively cheap. This study aims to determine changes in emission levels between motor vehicles using Catalytic Converters made from aluminum plates and without using Catalytic Converters. The method used is an experimental method by comparing the results of emissions testing before passing the Catalytic Converter and after passing the Catalytic Converter. The research process begins with the design of the Catalytic Converter Chasing Design, Catalyst Manufacturing and testing that consists of testing without Catalytic Converter and with Catalytic Converter which ends with data analysis and conclusion drawing.From the test results There is a decrease. • HC gas emission have decreased quite well by showing a percentage reduction of 20,36%, compared to the absence of a catalyst. • CO gas emission have decreased very well by showing a percentage reduction of 75%, compared with no catalyst. • CO2 gas emission decreased sufficiently by showing a percentage reduction of 3,16% • O2 has increased 32,32%. Keywords: catalytic converter, almunium gas emussions